Grouting method

By gelling the bleeding solution of suspension grouts containing slag and water glass, the method addresses the permeability and stability issues of existing suspension-type grouts, achieving effective soil consolidation and water stopping in fine-grained soils.

JP2025047867AActive Publication Date: 2025-04-03KYOKADO ENG CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023156622
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-04-03
Estimated Expiration
2043-09-22

AI Technical Summary

Technical Problem

Existing suspension-type grouts, particularly those using slag as an active ingredient, face challenges with permeability in fine-grained soils and stability during high-pressure injection, leading to insufficient consolidation and water stopping properties.

Method used

The development of a ground injection method that utilizes the gelling of the bleeding solution from suspension grouts, primarily composed of slag and water glass, to enhance permeability and stability, allowing for effective consolidation even in soils where suspended particles cannot penetrate.

Benefits of technology

This approach achieves improved permeability and environmental conservation, enabling integrated soil improvement and water stopping properties, while reducing environmental impact and carbon emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025047867000015
    Figure 2025047867000015
  • Figure 2025047867000016
    Figure 2025047867000016
  • Figure 2025047867000017
    Figure 2025047867000017
Patent Text Reader

Abstract

To provide a suspension-type ground-solidification material and a grouting method which are excellent in terms of environmental conservation, and which can have effects on solidifying ground and achieve integrated ground improvement and water cut-off property even in ground where suspended particles cannot penetrate.SOLUTION: There is provided a suspension-type ground-solidification material whose active ingredients are suspension particles made from slag or fly ash and water glass, wherein a bleeding liquid gelates and a sand gel, which has been soaked in the bleeding liquid, stands on its own.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a high-strength suspension-type ground consolidation material that contains slag or fly ash as an active ingredient and has permeable consolidation properties and environmental conservation properties, and to a ground grouting method.

[0002] The ground improvement method using slag-based suspension grout has a problem that it cannot penetrate between fine soil particles because it is mainly composed of suspended particles. Therefore, in the ground where fine-grained soil, which cannot be penetrated by suspended particles, is mixed, the consolidation effect cannot be obtained, and it is difficult to realize integrated ground improvement and water cutoff. In order to solve this problem, the present invention is a ground injection method that utilizes the gelation of the bleeding liquid of the suspension, and makes it possible to improve the ground where the penetration of the suspension cannot be expected. The present invention also relates to a ground consolidation material and a ground injection method that can be used in a high-pressure injection method by imparting a stable consolidation effect.Furthermore, the present invention relates to a ground improvement technology using a low-carbon grout injection method that uses a fine particle injection material mainly composed of fine particle slag in the ground.

[0003] The CO2 emissions during production of blast furnace slag, the main material of the ground consolidation material of the present invention, are about one-tenth of that of cement, and are expected to be more effective in reducing CO2 emissions than cement-based suspension-type injection materials.In addition, the present invention is a ground injection method that can be implemented economically by using industrial by-products as materials, and reduces the environmental burden, and is a technology that also contributes to carbon neutrality, which has become a national issue in recent years to prevent global warming. [Background technology]

[0004] Conventionally, high-strength ground improvement methods have been used to form high-strength consolidated bodies in the ground by high-pressure injection and mixing of cement-based grout. This method is excellent in that it forms large-diameter solidified bodies in the ground, but its principle is to mix and mix the soil in the ground with cement using high-pressure injection, replacing the soil particles with cement solidified bodies, which results in a large amount of discharged soil. The disposal of this soil poses challenges in terms of high costs and reducing CO2 emissions, which is an environmental problem from the perspective of carbon neutrality.

[0005] Conventionally, there have been proposed ground improvement methods in which finely divided cement or slag-based grout is injected into the ground to obtain high strength. However, these suspension-type grouts have the following problems when used in ground mainly composed of sand. (1) It is prone to clogging. Therefore, in ground that contains a mixture of fine soil or ground that consists of soil layers of different particle sizes, the penetration of suspended particles is insufficient, and the solidification and water-stopping properties are insufficient. (2) The finer the particles, the more they are electrically re-agglomerated, and the particle size becomes larger. As a result, the permeability is limited to the area around the injection tube, or the injection is pulsating. (3) Bleeding causes the suspended particles and mixed water to separate in the ground, making it difficult to form an integrated consolidated mass. (4) Because bleeding occurs, the solidification rate of the solidified material is small relative to the amount injected. (5) When using high-pressure injection, the injection force may disperse the injection material, resulting in insufficient solidification.

[0006] Furthermore, even if a dispersant is added to the fine particle suspension, the suspended particles separate from the mixing water during the process of high-pressure injection and mixing into the ground, so it is still difficult to form large, uniform aggregates.

[0007] Furthermore, suspension grouts made by mixing cement and water glass have been known in the past. However, such suspension grouts have a gelling time of about 1 to 10 minutes, and it is difficult to extend the gelling time any longer. In addition, durability is not obtained, and the suspended matter separates in the ground and causes clogging, or is injected in the form of veins, and the infiltration and solidification area is limited to the area around the injection pipe or is clogged, making it difficult to form a large, homogeneous solidified body.

[0008] The following describes the prior art relating to suspension grout. Conventionally, suspension grout made by mixing water glass and cement is known as LW, but it has a gel time of about 1 minute, high viscosity, and low strength. In addition, grout containing acidic silica sol obtained by mixing water glass and acid, cement, and hydrated lime is also known. This grout has a short gel time and is prone to flocculating, so it has poor permeability.

[0009] Furthermore, grouts containing the above-mentioned acidic silica sol and slag are also known. In this case, the slag acts as a neutralizer for the acidic silica sol to accelerate the gelation time, but does not contribute much to the strength.

[0010] For this reason, grout made by mixing low molar ratio water glass with slag cement has been developed, but although it has high strength, it has a gel time of about 10 minutes, is highly viscous, and has poor permeability when injected into soil. This is because when low molar ratio water glass is mixed with cement, its viscosity increases significantly, shortening the gel time, and the calcium content of the cement reacts with the water glass and is consumed, preventing it from reacting sufficiently with the slag.

[0011] Suspension grout can achieve higher strength than solution grout, but because it is made of particles, it has poor permeability to fine-grained soil. If this point could be improved and it could be widely applied to a wide variety of ground such as sandy ground, clayey ground, sandy soil containing fine particles, and ground mixed with gravel, its usefulness would be immeasurable.

[0012] In response to this, the present applicant has already developed grouts made of water glass and slag (Patent Documents 1 to 3). Although these grouts have excellent strength, they have the problem of insufficient permeability in fine-grained ground because they are suspensions. [Prior art documents] [Patent documents]

[0013] [Patent Document 1] Japanese Patent Application Publication No. 8-67875 [Patent Document 2] Patent No. 3413398 [Patent Document 3] Patent No. 6961270 Summary of the Invention [Problem to be solved by the invention]

[0014] The object of the present invention is to provide a suspension-type ground consolidation material and a ground injection method that have excellent penetration and consolidation properties and environmental conservation properties, and that can obtain a consolidation effect even in ground that cannot be penetrated by suspended particles, and that can realize integrated ground improvement and water stopping. [Means for solving the problem]

[0015] The invention described in Patent Document 1 is a ground injection solution consisting of water glass in a molar ratio of 2.8 or more, fine particle slag, and an alkali metal salt of hydrogen carbonate or carbonate. This invention has the effect of obtaining low viscosity and a long gelation time by using water glass, slag, and carbonate as well as carbonate, but has the problem that the strength is low because the alkalinity of the carbonate is weak, and because the carbonate is easily soluble in groundwater, if the carbonate dissolves in groundwater, the increase in strength is reduced.

[0016] In addition, the invention described in Patent Document 2 is a high-pressure injection method using grout made of water glass, slag, and hydrated lime. However, in the case of high-pressure injection, the injection liquid separates due to the injection action, resulting in poor solidification over a wide area and problems with the stability of gelation.

[0017] In order to solve the above problems of permeability and gelling stability in grouts containing slag as an active ingredient, the present inventors focused on Patent Document 3 by the same applicant and further developed it to complete the present invention.

[0018] The present inventors focused on the gelation of the bleeding liquid in order to solve the problem of the permeability of the suspension grout. In the conventional injection method, the particle size range of soil into which the suspension can be injected and the permeability range of the solution-type injection liquid have been discussed, but the bleeding of the suspension grout, its gelation, the strength of the gel, and the consolidation and strength of the sand into which the bleeding liquid has penetrated have not been paid attention. In addition, there has been no attention paid to the stability of consolidation when using slag-based grout in the high-pressure injection method. As a characteristic of the conventional suspension grout, the frequent bleeding was considered to be a drawback. The present invention focuses on this bleeding liquid to solve the problem of the permeability and consolidation of the suspension grout.

[0019] As described above, the present applicant has already proposed the techniques described in Patent Documents 1-3. These inventions have shown that slag-based grout can provide high strength and a long gel time. However, because it is a suspension, it is thought that the consolidation effect cannot be obtained in ground where suspended particles cannot penetrate. Also, when used in high-pressure injection mixing methods, the grout components are dispersed by the injection action, making it difficult to obtain stable consolidation.

[0020] The applicant has found the following through the above research: Although slag-based grouts can be summarized in Table 1, it was difficult to select materials and formulate them to ensure reliable penetration and solidification, because gel time, strength, permeation characteristics, sand particle size, permeation distance, and injection effect differ depending on the molar ratio and amount of water glass, slag particle size and Blaine value, Ca / SiO2 additive, slaked lime, carbonate, alkali bicarbonate, alkali aluminate, other salts, caustic alkali, cement, etc.

[0021] [Table 1]

[0022] The present inventors discovered in the applicant's previous application (Patent Document 3) that the portion of the injection liquid at the penetration front where the amount of slag is small gelled. Based on this phenomenon, the present inventors studied the gelling of the bleeding liquid, the self-supporting property of the homogel of the bleeding liquid, and the self-supporting property and strength of the sand gel by the bleeding liquid in order to improve the penetration and solidification property of the suspension grout. By using these conditions, the present inventors improved the penetration and solidification property of the suspension grout in fine-grained ground or sandy ground containing fine-grained soil, which was previously thought to be inapplicable, and completed the present invention.

[0023] First, the applicant paid attention to the penetration test in the specification of Patent Document 3 by the applicant (paragraphs

[0127] to

[0134] ,

[0149] , [Table 15], [Fig. 8], [Fig. 9], [Fig. 11] of Patent Document 3). In the penetration test of the slag-based grout described in Patent Document 3, it is shown that the grout containing slag penetrates up to 180 cm. It is also shown that gelation occurs even in the part with a low slag filling rate at the end of 180 cm, and it is also described that integration of the solidified bodies is possible. Furthermore, it is also described that a consolidated zone in which silica is consolidated even if it is weak in strength is formed on the outer periphery of the consolidated diameter with large strength, so that an integrated connected consolidated body with excellent water-stopping effect can be formed, and that the supernatant liquid of the bleeding gels. Furthermore, it is also described that a cement-based grout that does not gel causes bleeding in the ground and does not solidify unless the cement penetrates.

[0024] The present applicant further completed the present invention based on the following findings. (1) Range of penetration of fine-grained soil using solution-type grout (Figure 8). (2) Self-supporting homogel at low silica concentrations in solution-type grout, solidification of sand gel and self-supporting consolidated sand (Table 13). (3) Grain size distribution of the sand used in the infiltration test (Figure 9).

[0025] As described above, the present inventors have focused on the fact that a solidified body of the suspension with a high silica content is formed in the outer periphery where the suspension is injected in Patent Document 3, and adjacent solidified bodies are connected to each other. Conventionally, a large amount of bleeding in the suspension has been considered a drawback, but the present invention has focused on the fact that the bleeding liquid can penetrate between soil particles where suspended particles cannot penetrate, and conducted research on the gelation of the bleeding liquid. As a result, it was found that the gelation and strength of the bleeding liquid itself, the permeability of the bleeding liquid into the sand, and the strength of the sand gel have a significant effect on the improvement of the penetration and solidification of the suspension grout. Based on these findings, the conditions for the penetration and gelation of the bleeding liquid into areas where suspended particles could not penetrate, the homogel of the bleeding liquid, and the strength of the sand gel were found, and the above-mentioned problem of the penetration and solidification of the suspension grout was solved.

[0026] In addition, the present invention provides a ground consolidation method that uses a non-cement based ground consolidation material containing slag as the main component, thereby making it possible to obtain a solidified body with excellent durability and that is expected to have a CO2 reduction effect.

[0027] The present inventors have carried out specific research as follows. The present inventors have conducted research on gelation of the bleeding liquid of a suspension containing water glass and slag as active ingredients, or gelation of the bleeding liquid of a suspension containing water glass, calcium hydroxide, or gypsum as active ingredients, and on the penetration of suspended particles in a one-dimensional columnar penetration test and on consolidation by the bleeding liquid when water glass is included. From these results, it was found that the bleeding liquid can gel and consolidate even in areas where slag particles do not penetrate (Figs. 7, 5, and 6). In addition, a penetration consolidation test was conducted on a suspension containing slag but not containing water glass, and it was confirmed that gelation by the bleeding liquid does not occur. Furthermore, it was found that if the suspension contains salts, hydroxides, or chlorides of Ca, Mg, Al, etc. in addition to water glass, the bleeding liquid contains water-soluble Ca and Mg, which improves the gelation and self-supporting property of the bleeding liquid, and the self-supporting property and strength of the sand gel caused by the bleeding liquid.

[0028] The inventors have further researched suspensions containing slag and water glass as active ingredients, and grouts containing slag, water glass, and hydrated lime as active ingredients, and as a result have discovered that by using a formulation in which the bleeding liquid gels and the homogel made from the bleeding liquid has the strength to stand on its own, and / or in which the sand gel permeated with the bleeding liquid solidifies and has the strength to stand on its own, it is possible to consolidate ground that is impermeable to suspended particles, and to form an integrated consolidated body even under conditions in which it was previously difficult for suspended particles to penetrate.

[0029] As a result, even if the target injection area is ground with complex grain sizes, in sandy ground through which solution-type silica grout can penetrate, a solidified body can be formed that is integrated with the infiltrated area with a high-strength suspension, resulting in the inventing of a ground consolidation method using a low-carbon injection method that is high-strength, water-stopping, and environmentally friendly.

[0030] The present invention also provides a consolidation agent and an injection method that can be applied to high-pressure injection methods. The high-pressure injection method is a method in which a cement suspension is injected into the ground to replace the soil and sand in the ground, but it emits a lot of CO2 from the cement solidification material itself and the disposal of the ejected soil and sand. In contrast, the material used in the method of injecting slag-based grout into the ground is low-carbon grout, and the method can be called a low-carbon injection method. However, if slag and water glass are used as active ingredients in high-pressure injection, if the water glass is dislodged by the injection action, the alkali of the water glass will not work, and the slag will not be able to solidify. In contrast, if the active ingredients of the slag suspension are hydrated lime, gypsum, salts, oxides, and hydroxides of Ca, Mg, and Al, the slag itself will react with these and solidify sufficiently even without cement or water glass, and if water glass is added to it, the bleeding liquid itself will maintain sufficient self-supporting strength, and a stable solidification effect can be obtained even with the high-pressure injection method.

[0031] The ground consolidation material of the present invention is a suspension type ground consolidation material containing suspended particles made of slag or fly ash and water glass as active ingredients, The bleeding liquid is characterized in that the bleeding liquid gels and the sand gel permeated with the bleeding liquid becomes self-supporting.

[0032] In the present invention, it is preferable that the sand gel is self-supporting at a specimen size used in an unconfined compressive strength test. 2 More preferably, it is equal to or greater than this. Even on the surface of excavated ground, the solidifying effect of the bleeding liquid stops groundwater flow, and the solidified surface of the bleeding liquid remains undamaged and can stand on its own.

[0033] The ground consolidation material of the present invention preferably further contains a polyvalent metal compound. In addition, in the present invention, the molar ratio of the water glass is preferably 1.0 or more. In the present invention, the polyvalent metal compound is preferably one or more of hydroxides, oxides, or salts of Ca, Mg, or Al, and / or gypsum.

[0034] The ground consolidation material of the present invention has a Blaine value of 4000 to 15000 cm 2 It is preferable that the effective components are fine particle slag having a molar ratio of 1.0 to 5.0 / g and water glass having a molar ratio of 1.0 to 5.0.

[0035] It is preferable that the ground consolidation material of the present invention satisfies the following composition range so that the bleeding liquid permeates into the areas where the suspended particles have not yet permeated, gels, and consolidates the ground. The fine particle slug, (1) Blaine value is 4000-15000 cm 2 / g, (2) The blend amount is 50 to 150 kg / 400 liters; The water glass, (1) the molar ratio is 1.0 to 5.0; (2) The blending amount is 10 to 150 liters per 400 liters.

[0036] The ground consolidation material of the present invention further contains an alkaline agent, and it is preferable that the alkaline agent satisfies the following conditions. (1) Blaine value: 4000~13000cm 2 / g. (2) Compounding amount: 1~50kg / 400L.

[0037] In the present invention, it is preferable that the bleeding liquid gels at an SiO2 concentration of 0.5 w / v % or more.

[0038] In the present invention, the unconfined compressive strength of the solidified body permeated with the bleeding liquid is 2.0 kN / m after 7 days using a test piece of the size used in the unconfined compressive strength test. 2 As described above, it is preferable that the bleeding liquid penetrates into the areas where the suspended particles have not penetrated, gels, and solidifies the ground.

[0039] The ground injection method of the present invention is characterized by using the above-mentioned ground consolidation material of the present invention.

[0040] In the ground injection method of the present invention, the above-mentioned ground consolidation material of the present invention can be used in the high-pressure injection mixing method.

[0041] In the ground grouting method of the present invention, the improvement effect due to the solidification of the suspended particles can be confirmed by a non-destructive test, which is preferably performed by elastic wave velocity logging, acoustic tomography or surface wave exploration. Effect of the Invention

[0042] According to the present invention, it is possible to provide a suspension-type ground consolidation material and a ground injection method that have excellent penetration and consolidation properties and environmental conservation properties, and that can obtain a consolidation effect even in ground that cannot be penetrated by suspended particles, and that can realize integrated ground improvement and water stopping. [Brief description of the drawings]

[0043] [Figure 1] FIG. 1 is a photograph showing the bleeding state in Example 2. [Diagram 2] FIG. 2 is a photograph showing the bleeding state in Comparative Example 1. [Diagram 3] FIG. 1 is a photograph showing the state of Example 2 several days after permeation. [Figure 4] FIG. 1 is a photograph showing the state of Comparative Example 1 several days after penetration. [Diagram 5] 1 is a graph showing unconfined compressive strength versus permeation distance. [Figure 6] 6 is a graph showing an enlarged portion of the permeation distance of 90 cm to 120 cm in FIG. 5. [Figure 7] This is a photograph showing the state in which the bleeding liquid has gelled and the gel does not collapse (stands on its own) even when tilted. [Figure 8] This is a particle size accumulation curve for various on-site sands that have been treated with liquefaction countermeasures using solution-type grout. [Figure 9] 1 is a graph showing the particle size distribution of sand used in a permeation test. [Figure 10] FIG. 13 is a photograph showing the strength measurement situation on the 7th day in Example 14. [Figure 11] FIG. 13 is a photograph showing the state of the test specimen after strength measurement in Example 14. [Figure 12] 1 is a graph showing the relationship between the unconfined compressive strength (28-day strength) of Toyoura sand specimens consolidated with the grout of the present invention and the S-wave velocity measured by the bender element method. [Figure 13] 1 is a graph showing an example of the relationship between the number of curing days and the shear wave velocity. [Figure 14] This is an explanatory diagram for measuring S-wave velocity Vs and P-wave velocity Vp by installing receiving holes and transmitting holes in the consolidated zone or the zone expected to be consolidated. [Figure 15] 1 is a graph showing the relationship between unconfined compressive strength and S-wave velocity Vs in laboratory tests of consolidated specimens using field soil. [Figure 16] FIG. 1 is a photograph showing the device used in an indoor penetration test of a suspended ground consolidation material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0044] Hereinafter, an embodiment of the present invention will be described in detail. The ground consolidation material of the present invention is a suspension-type ground consolidation material containing suspended particles made of slag or fly ash and water glass as active ingredients.

[0045] The suspension grout used in the present invention is a suspension grout mainly composed of slag or fly ash. Examples of the hardener include silica solution, gypsum, slaked lime, salts or hydroxides exhibiting alkalinity, or salts or oxides of Ca, Mg or Al, caustic alkali, etc. Also, cement or the like may be added to adjust the consolidation time or strength. Furthermore, the ground consolidation material of the present invention preferably contains a polyvalent metal compound, and the polyvalent metal compound is preferably one or more of hydroxides, oxides or salts of Ca, Mg or Al, and / or gypsum.

[0046] In addition, polymeric thickeners such as polyacrylates, acrylic acid polymers, and CMC (carboxymethyl cellulose) can be added to these to increase viscosity and make them less likely to disperse even when sprayed at high pressure, and microbubbles or nanobubbles can be added to increase fluidity and form large solidified bodies.

[0047] As mentioned above, the non-cement-based hardening material containing slag and water glass as active ingredients exhibits high strength over a long gel time, as the alkali in the water glass acts on the ground granulated blast furnace slag, stimulating the latent hydraulic properties of the slag and the silica in the water glass causes gelation. The bleeding liquid can also gel to form a self-supporting homogel, or penetrate into sand to form a self-supporting sand gel. In this case, using a low molar ratio of water glass will further develop the latent hydraulic properties of the slag and obtain high strength. When using No. 3 water glass or a high molar ratio water glass, or when controlling the gel time, it is preferable to add chlorides or hydroxides of Ca, Mg, or Al.

[0048] Also, a material containing slag and an alkaline agent (for example, hydrated lime, dolomite, carbonates, or other alkaline salts) as active ingredients can be used. The above suspension type grout can be called low carbon grout (trademark registration number 6683218 by the present applicant).

[0049] In the above, the suspended particles may be slag and / or fly ash.

[0050] In addition to or in place of slag or fly ash, materials such as calcined sludge, dip-type clay, trip-type clay, volcanic ash, tuff, diatomaceous earth, calcined clay, etc., which react with sodium carbonate, Ca (calcium carbonate, calcium chloride, etc.) or Mg (magnesium chloride, magnesium carbonate, magnesium sulfate, etc.) and solidify through pozzolanic action, can be used. Furthermore, part of the slag or fly ash can be replaced with cement. Furthermore, water glass or a mixture of water glass and silica colloid can be used as the silica solution.

[0051] Furthermore, in recent years, from the perspective of preventing global warming, the realization of a low-carbon ground improvement method that uses non-alkaline cement or a reduced amount of cement has become an issue, but the above-mentioned solidification material can be said to be an environmentally friendly ground improvement method that solves this issue by using industrial by-products.

[0052] Furthermore, the present invention relates to the above-mentioned water glass-slag system, and to a cement and / or lime, particularly a cement having a specific surface area of ​​4000 cm 2 / g or more, preferably 8000 cm 2 / g or more and an average particle size of 10 μm or less, respectively, and further, a calcium elution regulator can be added and mixed to adjust the gelation time, permeability, or solidification strength.

[0053] Examples of calcium elution regulators mentioned above include sodium hydrogen carbonate, sodium carbonate, disodium hydrogen phosphate, and sodium hexametaphosphate, as well as their potassium salts, condensed phosphates as sequestering agents such as pyrophosphate, acid pyrophosphate, tripolyphosphate, tetrapolyphosphate, and acid metaphosphate, as well as sequestering agents such as ethylenediaminetetraacetate, nitrotriacetate, citrate, and tartrate, as well as ordinary phosphates such as sodium phosphate and sodium hydrogen phosphate, etc. Among these, soluble alkali agents such as bicarbonates, carbonates, and phosphates including condensed phosphates are particularly suitable.

[0054] In the present invention, any reactant capable of adjusting the gelation time may be used in combination. The reactants are as follows:

[0055] Esters: fatty acid esters of monohydric alcohols such as ethyl acetate, methyl acetate, butyl acetate, and amyl acetates. fatty acid esters of polyhydric alcohols such as ethylene glycol diacetate, glycerin triacetate, and succinic acid diester. total esters. intramolecular esters such as δ-butyrolactone and ε-caprolactone. cyclic esters: lactones. partial esters of polyhydric alcohols such as ethylene glycol monoformate, ethylene glycol monoacetate, ethylene glycol monopropionate, glycerin monoformate, glycerin monoacetate, glycerin monopropionate, glycerin diformate, glycerin diacetate, sorbitol monoformate, sorbitol monoacetate, glycolic acid monoacetate, and low-polymerization partially saponified vinyl acetate. unsaturated fatty acid esters such as diacetooxyethylene. carbonates such as cyclic carbonates such as ethylene carbonate, propylene carbonate, and glycerin carbonate.

[0056] Aldehydes: dialdehydes such as glyoxal, succinic dialdehyde, malondialdehyde, succinaldehyde, glutaric dialdehyde, and furfural dialdehyde.

[0057] Amides: formamide, dimethylformamide, acetamide, dimethylacetamide, propionamide, butylamide, acrylamide, malondiamide, pyrrolidone, caprolactam, and the like.

[0058] Alcohols: ethyl alcohol, methyl alcohol, amyl alcohol, glycerin, polyvinyl alcohol, etc., monohydric or polyhydric alcohols, or synthetic polymer alcohols.

[0059] Acids: Inorganic acids such as sulfuric acid, hydrochloric acid, phosphoric acid, etc. Organic acids such as formic acid, acetic acid, malonic acid, succinic acid, maleic acid, tartaric acid, etc.

[0060] Inorganic salts: Chlorides such as calcium chloride, sodium chloride, magnesium chloride, potassium chloride, and aluminum chloride; sulfates such as calcium sulfate, sodium sulfate, and aluminum sulfate; aluminates such as sodium aluminate and potassium aluminate; hydrochlorides such as ammonium chloride, zinc chloride, and aluminum chloride; chlorates such as sodium chlorate, potassium chlorate, sodium perchlorate, and potassium perchlorate; carbonates such as sodium carbonate, potassium carbonate, ammonium carbonate, sodium bicarbonate, potassium bicarbonate, and ammonium bicarbonate; bisulfates such as sodium bisulfate, potassium bisulfite, and ammonium bisulfite; sodium bisulfite, potassium bisulfite, and ammonium bisulfite. bisulfites such as ammonium, silicic acid salts such as sodium silicic acid and potassium silicic acid, silicates such as alkaline earth metal salts of silicate and aluminum salt, borates such as sodium borate, potassium borate, ammonium borate, hydrogen phosphates such as sodium hydrogen phosphate, potassium hydrogen phosphate, ammonium hydrogen phosphate, pyrosulfates such as sodium pyrosulfate, potassium pyrosulfate, ammonium pyrosulfate, pyrophosphates such as sodium pyrophosphate, potassium pyrophosphate, ammonium pyrophosphate, dichromates such as sodium dichromate, potassium dichromate, ammonium dichromate, permanganates such as potassium permanganate and sodium permanganate.

[0061] Organic salts: sodium acetate, sodium succinate, potassium formate, sodium formate, sodium citrate, etc.

[0062] Quicklime, alumina, iron oxide, magnesium oxide and other metal oxides, Ca, Al, Mg salts.

[0063] Furthermore, in the present invention, silica colloid, acidic silicic acid aqueous solution, and other optional gelling agents can be used in combination.Furthermore, pozzolans such as fly ash, siliceous earth, diatomaceous earth, and clay can be used in combination to formulate a ground injection liquid that takes advantage of the characteristics of each.In addition, a small amount of a dispersant can be used in combination to prevent settling, making a homogeneous solidified body.

[0064] When injecting the above-mentioned ground consolidation material of the present invention, for example, a one-component chemical solution with a long gelling time can be prepared and injected directly into the ground, or a cement-based or slag-based injection material can be injected into the ground in advance, and then the above-mentioned chemical solution can be injected into the injection site.

[0065] In addition, the water glass mixture liquid according to the present invention may be designated as liquid A, and the mixture liquid containing the fine particle slag according to the present invention may be designated as liquid B, and these two liquids A and B may be joined and injected. Alternatively, a mixture liquid containing the above-mentioned water glass and slag or further a calcium elution regulator may be designated as liquid A, and a gelation accelerator mixture liquid or any other optional gelling agent mixture liquid may be designated as liquid B, and these liquids A and B may be joined and the gelation time of the chemical solution may be adjusted as desired before injection.

[0066] Furthermore, a double injection pipe can be prepared, the chemical solution of the present invention with an adjusted long gelling time is designated as liquid A, and the gelling accelerator mixed liquid is designated as liquid B. First, both liquids A and B are pumped into the ground from separate pipes of the double injection pipe, and the two liquids are joined at the tip to make a grout with a short gelling time. This can then be injected into the gaps around the injection pipe to form a packer, and then only liquid A can be injected.

[0067] Furthermore, the water glass mixture of the present invention, or the mixture of water glass and slag, or these further containing a calcium elution regulator, may be designated as liquid A, the slow-setting reactant mixture as liquid B, and the quick-setting reactant mixture as liquid C. First, the grout having a short gelling time obtained by combining the two liquids A and B may be injected into the ground, and then the injection may be switched to the injection of the combined liquid AB, and the above steps may be repeated while increasing the injection stage.

[0068] Furthermore, water glass and slag (which may contain a calcium elution regulator as necessary) can be used as liquid A, a liquid containing a fast-setting reactant can be used as liquid C, and a fast-setting grout made from the AC combined liquid can be injected into the ground from the upper outlet of the double pipe, and a slow-setting grout made from liquid A can be injected into the ground from the lower outlet.

[0069] Furthermore, a chemical solution having a long gelling time of several hours can be prepared by adding slag to water glass and, if necessary, a calcium elution regulator, and a mixed liquid containing slag and / or other reactants can be prepared as Chemical Solution A, and Chemical Solution B can be added to Chemical Solution A during construction to prepare a chemical solution of the present invention having a prescribed gelling time and strength, which can then be injected into the ground.

[0070] Furthermore, it is also possible to perform composite injection by injecting a quick-setting grout made of AC combined liquid into the ground, after injecting a slow-setting chemical solution made of BD combined liquid, with No. 3 water glass mixed solution with a molar ratio higher than 2.8 as solution A, a water glass mixed solution with a molar ratio in the range of 1.0 to 5.0 as solution B, a quick-setting reactant mixed solution as solution C, and a fine particle slag mixed solution according to the present invention as solution D. From the viewpoint of solidification strength and viscosity, the concentration of water glass is appropriate to be about 1.5 to 20% as SiO2 component in the total chemical solution.

[0071] The slag, gypsum and lime used in the present invention are useful for adjusting the gelation, viscosity and solidification strength of the water glass, respectively. However, the size of these particles is important. The average particle size is 10 μm or less, and the specific surface area is 5000 cm. 2 / g or more, preferably 8000 cm 2At a silica content of 10000g or more, the large silica particles in the slag, the small silica particles in the water glass, and calcium combine with an appropriate amount of alkaline water glass as a stimulant to form a strong, dense composite silica-calcium gel.

[0072] In other words, the small silica particles originating from the water glass fill the spaces in the net of large silica particles originating from the slag, and these are linked and solidified by calcium to form a dense hardened material.

[0073] Furthermore, when a calcium elution regulator is added to the system of the present invention, for example, when a carbonate, bicarbonate or phosphate is added, inactive calcium carbonate or calcium phosphate is formed, which can delay gelation.

[0074] In the above, if the molar ratio of water glass is lower than 1.0, the alkali content becomes excessive, and gelation does not occur, or the gelation time is extended to an extent that it is not practical as a pouring material, resulting in insufficient solidification, or the viscosity increases, and clear gelation does not occur while the viscosity remains increased. Therefore, the molar ratio of water glass is preferably 1.0 or more.

[0075] When the molar ratio of water glass is more than No. 3 water glass, that is, when the molar ratio is more than about 2.8, the amount of alkali in the water glass is small, and the amount of alkali is insufficient to stimulate the latent hydraulic properties of the slag and harden it, so the slag cannot develop its inherent strength. As a result, the water glass and slag do not react easily, and not only does the gelation period take a long time, but the slag and water glass separate, making it difficult to obtain a homogeneous solidified body. However, when slaked lime, gypsum, or alkali is added, the slag hardens.

[0076] Furthermore, if the particle size of the slag is coarser than the above range, the reaction between the alkali and Ca content of the water glass and the slag is significantly reduced, so that gelation does not occur within the range suitable for injection, and furthermore, the alkali-induced solidification of the water glass is insufficient.

[0077] That is, according to the present invention, the average particle size is 10 μm or less and the specific surface area is 5000 cm 2 By using fine particle slag with an active reactivity of 100000000000 / g or more and water glass, the bleeding liquid gels and the sand gel permeated with the bleeding liquid becomes self-supporting, it is possible to obtain a wide range of gelation times and excellent permeability to fine soil for the first time.

[0078] Moreover, it was found that the gelation time can be effectively shortened by using gypsum and / or lime, dolomite, or salts or oxides of Ca, Mg, or Al in combination with such a water glass and slag system, and further, by using a calcium elution regulator in combination, it is possible to increase the strength of the sand gel permeated with the bleeding liquid and effectively delay the gelation time, thereby making it possible to easily control the gelation time.

[0079] When the molar ratio of water glass is lower than 1.0, a very large amount of lime or cement is required to shorten the gelation time, and the viscosity increases significantly, resulting in a thixotropic behavior, which significantly reduces the permeability. Moreover, it is impossible to significantly shorten the gelation time.

[0080] In contrast, in the range of water glass according to the present invention, even small amounts of gypsum, lime, salts of Ca, Mg, and Al, or their oxides or hydroxides can be added to effectively shorten the gelation time. Therefore, there is no significant increase in viscosity, and therefore no inhibition of permeability. In addition, in the range of water glass according to the present invention, slag can maintain a low viscosity in the presence of water glass without exhibiting thixotropic properties like cement and lime. This is thought to be because the CaO in the slag contains little CaO that is easily liberated like cement and lime, and it is liberated only when a certain amount or more of alkali is present in the water glass.

[0081] In order to solve the above problems, the present invention provides a ground grouting method for consolidating the ground using a ground consolidation material containing slag and preferably water glass at a molar ratio of 1.0 or more as active ingredients, in which the bleeding liquid of the grouting liquid gels and the sand gel penetrated by the bleeding liquid has a strength that allows it to stand on its own, so that even if the suspended particles are dispersed or become vein-like, the upper solution integrates the solidified parts of the suspended particles, and the consolidation rate of the grouting liquid can be increased. In addition, since the mixture of slag and gypsum and / or slaked lime forms a high-strength solidified body by itself, the addition of water glass to the suspension can further improve the stability and reliability of the consolidation. Furthermore, a solidified body that is difficult to disperse even when a polymer-based thickener is added can be formed, and the addition of microbubbles (or nanobubbles) can improve the permeability by their rolling action.

[0082] Furthermore, the inventors have found that in order to use slag-based grout for high-pressure injection, it is necessary for the injection material to be difficult to disperse under the injection force and to be accompanied by reliable solidification, and that for this purpose, the bleeding liquid of the suspension itself must gel, and the sand gel permeated with the bleeding liquid must have the strength to stand on its own. Furthermore, the strength of this material was found to be 2.0 kN / m after 1 to 7 days in a uniaxial compression test. 2 It has been found that it is necessary to use the above blending recipe.

[0083] The present invention is a method for determining the Blaine value of 4000 to 15000 cm 2 The preferred ground consolidation material is a suspension type ground consolidation material containing as active ingredients fine particle slag of 0.1 g / g and water glass in a molar ratio range of 1.0 to 5.0, or a suspension type ground consolidation material further containing as active ingredients one or more of an alkali additive, gypsum, calcium hydroxide, salts of Ca, Mg, Al, or their oxides or hydroxides, and by satisfying the following conditions A and B, the bleeding liquid permeates into the parts of the ground consolidation material that the suspended particles have not been able to permeate, and gels to consolidate the ground.

[0084] A. Composition range of ground consolidation materials 1. Fine particle slag (1) Blaine value: 4000~15000cm 2 / g (2) Mixture amount: 50-150 kg / 400 liters (3-16 w / v%) 2. Water glass (1) Molar ratio: 1.0 to 5.0 (2) Mixing amount: 10-150 liters / 400 liters 3. When using the following alkaline agents in combination: (1) The Blaine value of alkaline agents, especially calcium hydroxide or gypsum: 4000 to 13000 cm 2 / g. (2) Compounding amount: 1~50kg / 400L.

[0085] B. The bleeding liquid gels, and the sand gel permeated with the bleeding liquid solidifies and becomes self-supporting. Here, the sand gel is preferably self-supporting at a specimen size used in an unconfined compressive strength test, and is preferably capable of standing on its own at an unconfined compressive strength of 2.0 kN / m 2 In the present invention, the unconfined compressive strength of the solidified body permeated with the bleeding liquid is 2.0 kN / m2 after 7 days using a test piece of the size used in the unconfined compressive strength test. 2 As described above, it is preferable that the bleeding liquid penetrates into the areas where the suspended particles have not penetrated, gelling and solidifying the ground.

[0086] In the ground consolidation material of the present invention, the bleeding liquid preferably gels at an SiO2 concentration of 0.5 w / v % or more.

[0087] Table 2 shows the component values ​​of general water glass, and the molar ratios were calculated from the values ​​of silicon dioxide and sodium oxide. In the present invention, the water glass may be one in which sodium is added to water glass with a molar ratio of 1.0 or more to lower the molar ratio. Furthermore, colloidal silica can be added to water glass with a molar ratio of 1.0 or more to increase the molar ratio of the silica solution containing water glass as an active ingredient. In this case, the molar ratio of the water glass to which silica colloid has been added is 5.0 or more, and the molar ratio can be increased to about 100. Even without using a combination, the molar ratio of silica colloid is 103. The molar ratio of water glass can also be 100 or more.

[0088] The specific surface area, average particle size and particle size of slag are shown in Table 3, and those of hydrated lime in Table 4. These are representative examples.

[0089] Here, the high molar ratio water glass refers to water glass having a molar ratio higher than 2.8, whereas the low molar ratio water glass has a molar ratio of 2.8 or less.

[0090] [Table 2]

[0091] [Table 3]

[0092] [Table 4]

[0093] The ground injection method of the present invention is characterized by using the above-mentioned ground consolidation material of the present invention. In particular, the ground injection method of the present invention is preferably used for the high-pressure injection mixing method.

[0094] In the ground grouting method of the present invention, the improvement effect due to the solidification of the suspended particles can be confirmed by non-destructive tests such as elastic wave velocity logging, acoustic tomography, and surface wave exploration.

[0095] The present invention forms a consolidated area of ​​a suspended type ground consolidation material over a wide area in the ground, and consolidates the ground over a wide area. The inventors have found that the consolidated ground is effective for confirming the improvement effect by the elastic wave velocity logging and acoustic tomography.

[0096] Since the suspension-type ground consolidation material of the present invention has the following properties related to strength and permeability, it has been found that elastic wave velocity logging is extremely effective in understanding the ground improvement effect of this suspension.

[0097] (Relationship between uniaxial compressive strength and elastic wave velocity using bender elements) A specific description will be given below. Fig. 12 shows the relationship between the unconfined compressive strength (strength at 28 days) and the S-wave velocity measured by the bender element method in Toyoura sand specimens consolidated with the ground consolidation material of the present invention. FIG. 13 shows an example of the relationship between the number of curing days and the shear wave velocity.

[0098] FIG. 14 is an explanatory diagram for measuring the S-wave velocity Vs and the P-wave velocity Vp by installing receiving holes and transmitting holes in the consolidated zone or the zone to be consolidated. The injection hole may be used as the receiving hole and the transmitting hole to measure the S-wave velocity Vs and the P-wave velocity Vp. In laboratory tests, the S-wave velocity Vs and P-wave velocity Vp are measured using the bender element method, with transmitter and receiver elements installed at both ends of a solidified specimen, but on-site, the S-wave velocity Vs and P-wave velocity Vp are measured using surface wave exploration and velocity logging.

[0099] Since the strength of the ground consolidation material of the present invention is determined almost exclusively by the amount of suspended particles in the suspension, the improvement effect can be estimated by knowing the amount of suspended particles and the S-wave velocity Vs and P-wave velocity Vp.

[0100] The relationship between the unconfined compressive strength and S-wave velocity Vs in laboratory tests on consolidated specimens using in-situ soil, and the relationship between the amount of suspended particles in the suspension and the unconfined compressive strength are shown in Figure 15, where the measured values ​​of S-wave velocity at points A and B in the injected ground are plotted. From this, we can estimate the unconfined compressive strength at points A and B. We can also estimate the amount of suspended particles in the suspension at those points.

[0101] In this way, the extent and strength of solidification at the injection site can be grasped. In the example of Figure 15, it can be seen that the target S-wave velocity Vs is satisfied at points A and B, and therefore the design Vs is satisfied.

[0102] In addition, if the relationship between the filling rate and content of the suspended particles and the S-wave velocity and P-wave velocity is obtained in the laboratory test, the unconfined compressive strength can be used to determine the filling amount and composition in the ground from the measured values ​​of the S-wave velocity and P-wave velocity in the field. Figure 16 shows the device used in the laboratory permeation test of the suspended ground consolidation material of the present invention, and Figures 3 and 4 show the state after a one-dimensional injection test with a mold length of 1.5 m. Figure 5 shows the unconfined compressive strength corresponding to the permeation distance. From the results of this unconfined test, the shear wave velocity of the consolidated body at each permeation distance can be known from Figure 12. In addition, the amount of suspended particles filled in the ground can be known.

[0103] In addition, the results can be useful in analyzing non-destructive testing by comparing the penetration test values ​​of the injected ground before and after injection, the strength test values ​​of the specimen obtained by core sampling, and the estimated shear wave velocity and strength at that point (Figure 15).

[0104] Furthermore, if the receiving and transmitting units are installed before injection (Fig. 14), the seepage situation in the ground can be grasped in real time during injection, making it possible to correct the injection amount and the mixture amount of suspended particles in real time.By non-destructively measuring the S-wave and P-wave velocities that change with curing, it is possible to determine whether the desired improvement effect has been achieved.

[0105] As described above, the flow characteristics, injection design, and injection effects of the ground consolidation material of the present invention can be understood and incorporated into the design.

[0106] The test results are shown below.

[0107] (Test Method) 1. Consolidation material test materials The materials of the binders used are listed below. No. 3 water glass: specific gravity 1.41, silica concentration 29 w / w%, molar ratio 2.9. No. 1 water glass: specific gravity 1.35, silica concentration 21 w / w%, molar ratio 2.0. Slaked lime: Specific gravity 2.5. Slag: specific gravity 2.9, Blaine value 8000cm 2 / g. Sodium aluminate: Specific gravity 1.6. Gypsum: specific gravity 2.16. Fly ash: Specific gravity 2.15. Cement: Specific gravity 3.0. Colloidal silica: Specific gravity 1.2.

[0108] 2.Composition The formulations used in the tests are shown in Tables 5 to 12. The results are the same when using one shot formulation.

[0109] [Table 5]

[0110] [Table 6]

[0111] [Table 7]

[0112] [Table 8]

[0113] [Table 9]

[0114] [Table 10]

[0115] [Table 11]

[0116] [Table 12]

[0117] (Fluidity test) The gelation time was measured by the inverted cup method, and the gelation time was determined as the time when the solution no longer flowed when the cup was tilted or when the viscosity reached 100 mPa·s on the viscometer.

[0118] Tables 5 to 12 show the gel times for each formulation.

[0119] (Breeding test) A specified amount was poured into a φ5×50 cm polyethylene bag (grout bag), and measurements were performed in accordance with JSCE-F-522-2013 to measure the bleeding rate. The results are shown in Table 13. In addition, the presence or absence of gelation of the bleeding liquid when measuring the bleeding rate was confirmed.

[0120] Here, the bleeding rate = 100 × (L1 / L), and is calculated as L = L1 + L2. L1: Length of gel bleeding liquid L2: Length of the suspended particle section L: Length of the solidified suspension

[0121] In the bleeding test, the color changed to blue-black over time, indicating that the hydration reaction was progressing. It was also confirmed that the bleeding part at the top had become opaque and solidified due to gelation (see Figure 1). On the other hand, in the comparative example shown in Figure 2, the bleeding part was transparent and did not gel.

[0122] (Strength test) (Preparation of sand gel specimen) Using No. 6 silica sand and bleeding liquid, specimens with a diameter of 5 cm and a height of 10 cm were prepared by the mixing method so that the relative density was 60%, and the unconfined compressive strength was measured after 28 days. Table 13 shows the bleeding rate and the strength of the sand gel using the bleeding liquid.

[0123] The bleeding rate is higher when the amount of water glass is larger, and is higher when the amount of slag is smaller. In the sand gel using the bleeding liquid, the strength was higher when the amount of water glass and slag was larger. In addition, Example 7 is Example 2 with the addition of gypsum, and the bleeding rate decreased and the strength increased when gypsum was added.

[0124] The gelation of the bleeding liquid and its self-supporting property, as well as the strength and self-supporting property of the sand solidified by the bleeding liquid (sand gel) vary depending on the amount of slag and water glass in the suspension, the silica concentration (SiO2) of the water glass and the ratio of CaO content of the slag (CaO / SiO2), the gel time, and the particle size and density of the sand solidified by the bleeding liquid. Therefore, in order to integrate the self-supporting property of the sand gel, which includes these various factors, and the fine-grained soil parts where the penetration and solidification of the suspended particles was difficult or the parts where the penetration did not occur, a test was conducted to find the minimum value of the strength of the sand gel permeated with the bleeding liquid, with the condition that the sand gel is self-supporting. Table 13 shows the measurement results of the strength of the sand solidified by the bleeding liquid, together with the bleeding rate (%).

[0125] [Table 13]

[0126] From these results, it was found that the gelation occurred whether the bleeding rate was more than 50% or less than 50%, and the bleeding liquid penetrated the composition, resulting in a composition that allowed the sand gel to stand on its own. The minimum strength at which the sand gel could stand on its own was 2.0 kN / m 2 The strength of the self-supporting sand gel made of only slag and water glass (Example 14) was 15 kN / m on the 28th day. 2 It was also found that the strength of the sand gel would be further increased if the bleeding solution contained salts such as Ca, Mg, and Al.

[0127] For Example 14, the strength was also measured on the first and seventh days. The strength on the first day was 2.0 kN / m 2 On the 7th day, the strength was 10 kN / m 2 A similar tendency was also obtained with Toyoura sand. In the present invention, the test specimen is adjusted to the size of the specimen for the uniaxial compression test of soil, with the diameter D0 (mm) usually being 35mm or 50mm, and the height H0 (mm) being 1.8 to 2.5 times the diameter D0 (mm). As long as it is a self-supporting sand gel, judgment can be made at any age. Figure 10 shows the test conditions. From this, it was found that even with on-site sand, a 2.0kN / m 2 It was found that if the strength of the improved ground is obtained, the soil will be self-supporting. 3 The amount of injection liquid per unit is 0.4 m 3 It becomes. Figure 11 shows the condition of the test specimen after the test was completed.

[0128] In Examples 1 to 7, the gel time was shortened as the amount of added slaked lime increased, and the strength increased as the amount of slag increased. In Example 8, the entire composition gelled, and the bleeding portion also solidified. In Comparative Example 1, the solidified portion solidified, but the bleeding portion did not gel. In Example 9, the bleeding portion also gelled, but the gel time was longer than that of Example 8. Example 10 was a combination of a low molar ratio and hydrated lime, and gelation of the bleeding liquid was confirmed. In Example 11, fly ash was used instead of slag. The bleeding liquid gelled in the same way as in the case of slag. In Examples 12 and 14, although there was no clear gelation time, the bleeding liquid eventually gelled and gelled. The bleeding liquid of Example 13 gelled. In Comparative Example 2, there was no clear gel time, and the bleeding liquid did not gel. The bleeding liquid of Example 15 gelled. It was found that the bleeding liquid also gelled when colloidal silica and water glass were used in combination. If the sand gel using the bleeding liquid does not stand up, the slag will not be able to penetrate completely, and the ground will not become integrated and will harden.

[0129] The sands used in the one-dimensional infiltration test were No. 5 silica sand, No. 6 silica sand, No. 7 silica sand, and Toyoura sand. Their particle size distribution is shown in Figure 9. In addition, these sands were filled into a long mold of 2 m or 1 m in length with different relative densities, and the infiltration test was carried out.

[0130] (Relationship between silica concentration and strength) The neutral to alkaline chemical solutions used in Table 13 were poured into an acrylic mold with a removable bottom and allowed to solidify, and the presence or absence of gelation for each silica concentration of homogel and the self-supporting ability of the gel were confirmed. The same procedure was also carried out with sand gel, and the solidification and self-supporting ability of the consolidated sand were confirmed. The results are shown in Table 14.

[0131] At silica concentrations below 0.5%, the homogel and sand gel did not become self-supporting. Further testing revealed that gelation occurred even at a silica concentration of 0.25%.

[0132] [Table 14]

[0133] Figure 7 shows the state in which the bleeding liquid has gelled and remains self-supporting even when tilted. Even if the entire amount of the bleeding liquid has not gelled, the gel remains self-supporting even when tilted in the same way, as with the sand gel.

[0134] (Permeability test) (Test equipment and test method) Using a one-dimensional infiltration apparatus (length 2m), infiltration tests were carried out on No. 6 silica sand to investigate the infiltration length and strength distribution. Test conditions: Acrylic mold h=2m, mixed liquid 3L After the sample was saturated with water, the suspension was poured into the bottom until no more liquid was discharged.

[0135] The experiments were carried out using the compositions of Example 2 and Comparative Example 1 (FIGS. 3 and 4).

[0136] Figure 3 shows the results for the formulation of Example 2. It was possible to measure the strength even at a penetration distance of 120 cm. The sand gel did not discolor beyond 90 cm, but it is believed that the reason the strength could be measured is because the bleeding liquid solidified beyond 90 cm (Figures 5 and 6). From Table 14, it is believed that the portion beyond 90 cm contains 0.5% or more silica.

[0137] Figure 4 shows the results of the test using the formulation of Comparative Example 1. The strength could be measured up to 90 cm, but there was no discoloration after 90 cm, so the strength could not be measured and it was found that the bleeding liquid had not gelled.

[0138] In the penetration test, the areas where there was no discoloration of the slag were thought to be areas where the slag had not penetrated, and it was found that the Ca content was not enough to cause the bleeding fluid to gel.In contrast, in Figure 3, it is presumed that the Ca and silica content was enough to cause the bleeding fluid to gel, become self-supporting, and develop strength by the sand gel being self-supporting.

[0139] From the above, under conditions where the soil particle size density and the particle size distribution of the suspended particles are unable to penetrate between the soil particles, only the bleeding liquid will penetrate. And, if the particle size of the ground that the bleeding liquid can penetrate is within the range of the particle size accumulation curve of the on-site sand in Figure 8, it can be seen that penetration and solidification will occur.

[0140] From Figure 6, even if the penetration distance of the suspended particles in the suspension is just under 90 cm, the bleeding liquid will penetrate up to 120 cm, and if the bleeding liquid has the strength to stand on its own or the sand gel has the strength to stand on its own, it can be predicted that the silica concentration is 0.5 to 2% or more. Therefore, with an injection hole spacing of 30 x 2 = 60 cm, the homogel of the bleeding liquid will connect the consolidated bodies penetrated by the suspended particles that have high strength to stand on their own.

[0141] In this way, an integrated solidified body can be formed even under ground conditions in which suspended particles cannot penetrate, and even if the injection hole spacing is wide, the solidified bodies between the holes can be connected by the self-supporting gel of the bleeding liquid, forming an integrated solidified ground.

Claims

1. A suspension-type ground consolidation material containing suspended particles made of slag or fly ash and water glass as active ingredients, A ground consolidation material characterized in that a bleeding liquid gels and the sand gel permeated with the bleeding liquid becomes self-supporting.

2. 2. The ground consolidation material according to claim 1, wherein the sand gel is self-supporting at a specimen size used in a uniaxial compressive strength test.

3. The uniaxial compressive strength of the sand gel is 2.0 kN / m 2 The ground consolidation material according to claim 2.

4. The ground consolidation material according to claim 2, further comprising a polyvalent metal compound.

5. 3. The ground consolidation material according to claim 2, wherein the molar ratio of said water glass is 1.0 or more.

6. 5. The ground consolidation material according to claim 4, wherein the polyvalent metal compound is one or more of hydroxides, oxides, or salts of Ca, Mg, or Al, and / or gypsum.

7. Blaine value is 4000 to 15000 cm 2 4. The ground consolidation material according to claim 3, comprising as active ingredients fine particle slag having a molar ratio of 1.0 to 5.0 / g and water glass.

8. The ground consolidation material according to claim 7, which satisfies the following composition range, so that the bleeding liquid permeates into the areas where the suspended particles have not yet permeated, gels, and consolidates the ground. The fine particle slug, (1) Blaine value is 4000 to 15000 cm 2 / g, (2) The blending amount is 50 to 150 kg / 400 liters; The water glass, (1) the molar ratio is 1.0 to 5.0; (2) The blending amount is 10 to 150 liters / 400 liters.

9. 9. The ground consolidation material according to claim 8, further comprising an alkaline agent, which satisfies the following conditions: (1) Blaine value: 4000 to 13000 cm 2 / g. (2) Blend amount: 1-50kg / 400L.

10. The bleeding liquid is SiO 2 2. The ground consolidation material according to claim 1, which gels at a concentration of 0.5 w / v % or more.

11. The unconfined compressive strength of the solidified body permeated with the bleeding liquid is 2.0 kN / m2 or less after 7 days using a test piece of the size used in the unconfined compressive strength test. 2 The ground consolidation material according to claim 1, wherein the bleeding liquid permeates into the areas where the suspended particles have not yet permeated, gelling and consolidating the ground.

12. A ground injection method using the ground consolidation material according to any one of claims 1 to 11.

13. A ground injection method, comprising using the ground consolidation material according to any one of claims 1 to 11 in a high-pressure injection mixing method.

14. 13. The ground grouting method according to claim 12, wherein the improvement effect due to the solidification of the suspended particles is confirmed by a non-destructive test.

15. The ground grouting method according to claim 14, wherein the non-destructive testing is carried out by elastic wave velocity logging, acoustic tomography or surface wave exploration.

Citation Information

Patent Citations

  • Chemical for injecting into ground

    JP1996067875A

  • Ground consolidation process

    JP2002088752A

  • Ground consolidation material and ground improvement method

    JP2022066686A

  • Ground consolidation construction method

    JP3413398B2

  • Ground consolidation materials and ground improvement methods

    JP6961270B1